Building a Critical Thinking Generation: Developing an Innovative History Learning Model - Abrar, Abrar; Marta, Nur Aeni; Yanuardi, M Hasmi; Fakhruddin, M; Risqi, Firlyda; Rohana, Melda Amelia; Santosa, Yusuf Budi Prasetya (Diakronika, 2025)
In this digital era, many historical narratives are vulnerable to misinformation and biased interpretations that circulate freely on social media and online platforms. This requires students to develop critical thinking skills that can be improved through history learning. This study aims to develop teaching materials based on conceptual achievement and creative problem-solving models to improve students' critical thinking skills in history learning. The method used in this study is R&D with the ADDIE model. In the analysis stage, the process involves identifying core problems and understanding students' needs. The design stage focuses on planning teaching materials. The actual instructional product is created during the development stage, including content, media, and student activities. The implementation stage involves testing the developed teaching materials in a real classroom environment (conducted on 32 grade XI students of SMA Labschool Jakarta). Finally, the evaluation stage assesses the effectiveness of the teaching materials in meeting the intended learning objectives. The study's results showed that the developed teaching materials effectively improved students' critical thinking skills, as evidenced by a significant increase in pretest and posttest scores (p-value < 0.05). Further effectiveness was measured using N-gain analysis, which indicated effectiveness in the moderate category, with a 32% increase. Expert validation from content and media specialists also confirmed a very high level of feasibility (> 80%). Thus, teaching materials focusing on conceptual achievement and creative problem-solving can be an alternative to traditional history learning, encouraging students to think critically and gain a deeper understanding of history.